Respuesta :
Answer: 4
Step-by-step explanation: First convert the equation to y = mx + b form.
Start by subtract 4x from both sides to get -y = -4x + 3.
From here, divide both sides by -1 to get y = 4x - 3.
Now in y = mx + b form, the slope is the multiplier, or the m.
So here, 4 is the slope.
Answer:
(D) 4
Step-by-step explanation:
In order to find the slope you need to rearrange the equation so that y is alone on one side, so:
4x - y = 3
-y = -4x + 3
y = 4x - 3
The slope is the coefficient in front of x, so the slope is 4